2008
DOI: 10.1007/s10585-008-9187-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing contributes to the loss of BRMS1 expression in breast cancer

Abstract: Breast Cancer Metastasis Suppressor 1 (BRMS1) suppresses metastasis of human breast cancer, ovarian cancer and melanoma in athymic mice. Studies have also shown that BRMS1 is significantly downregulated in some breast tumors, especially in metastatic disease. However, the mechanisms which regulate BRMS1 expression are currently unknown. Upon examination of the BRMS1 promoter region by methylation specific PCR (MSP) analysis, we discovered a CpG island (−3477 to −2214), which was found to be hypermethylated acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 51 publications
4
56
1
1
Order By: Relevance
“…This observation has led to exploration of the promoter methylation patterns for the metastasis suppressors. The BRMS1 promoter contains several CpG islands which can become methylated and effect gene expression [34]. Chimonidou et al recently assessed CTC from breast cancer patients for BRMS1 expression and BRMS1 promoter methylation and found that reduced expression and promoter methylation correspond to probability of recurrence from metastasis and survival [35].…”
Section: Brms1mentioning
confidence: 99%
“…This observation has led to exploration of the promoter methylation patterns for the metastasis suppressors. The BRMS1 promoter contains several CpG islands which can become methylated and effect gene expression [34]. Chimonidou et al recently assessed CTC from breast cancer patients for BRMS1 expression and BRMS1 promoter methylation and found that reduced expression and promoter methylation correspond to probability of recurrence from metastasis and survival [35].…”
Section: Brms1mentioning
confidence: 99%
“…Structural analysis of the BRMS1 promoter has revealed the presence of two hypermethylated cytosinephosphoguanine (CpG) islands (Metge et al, 2008). Hypermethylation of CpG islands restricts the activity of the BRMS1 protein, mainly due the tightly packed nucleosomes (Metge et al, 2008).…”
Section: Transcriptionmentioning
confidence: 99%
“…Hypermethylation of CpG islands restricts the activity of the BRMS1 protein, mainly due the tightly packed nucleosomes (Metge et al, 2008). Gene expression can also be suppressed by blocking transcription factor binding.…”
Section: Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several years the extensive research carried out on the mechanisms of metastases formation concentrated on circulating tumor cells(CTC). The modern understanding of cancer biology and process of metastasis suggest that these circulating cells play a vital role in forming metastatic disease (Metge et al 2008).…”
mentioning
confidence: 99%